In-vivo and In-vitro Activities of Medicinal Plants on Ecto, Endo and Haemoparasitic Infections: A Review - Mbaya, Albert Wulari; Ogwiji, Mathew (Current Clinical Pharmacology, 2014)
Crude methanol, pet. ether, ethyl acetate, n-hexane, dichloromethane and aqueous extracts of various species of medicinal plants have shown significant in-vivo and in-vitro pharmacological activities against ecto, endo and haemoparasites. The scientific evaluations of the use of the plants as antiparasitic agents were based on the claims of folklore drawn from traditional healers from various communities across the world. The pharmacological activities of these plants were associated with the presence of various bioactive compounds such as alkaloids, flavonoids, saponins, glycosides, allicinine, harmala, harmaline, harman, tetrahydroharman, ursolic acid, terapines, tannins, phenolic compounds, embelin and brucine. These compounds were either found in the leaves, seeds, bulbs, flowers, stem, root barks or entire plant. In the in-vivo studies, plant extracts were tested using animal models such as mice, sheep, goats, cattle and dogs. The in-vivo anthelmintic activities of the plants were assessed by faecal egg out puts and post-mortem worm counts which in most instances achieved 70-90% priori levels with some of the plants. For haemoparasitic infections, parasitaemia clearance levels were used, while larvae and adult deaths were used to measure the activity of the plants against ectoparasites. For in-vitro activities, inhibitory concentration IC50 values using the brine lethality test, micro dilution, flow cytometery and larval packet test were used to assess the efficacy of the plant extracts on the parasites in various cell cultures. Significant in-vitro activity of 99.8% at 3.1mg/ml was achieved with the ethanolic extract of Azadirachta indica. Many of the plants were found to be more potent and possessed similar mechanism of action as their novel synthetic drugs. Such breakthroughs have led to the development of less toxic, cheaper and readily available drugs. Worthy of note is the use of the fruit of the Thai plant Piper longum (PIPERACEAE) as part of a drug formulation used in India for the treatment of clinical giardiosis in human patients.
Keywords: in-vivo